Flavonoid Level Analysis Of Ethanol Extract Of Papaya Leaves (Carica papaya L.) And Its Application As An Anti-Pain In Test Mice (Mus musculus) - Nur Ainun; Sarni; Wa Ode Syafriah (International Journal of Multidisciplinary Learners, 2024)
Papaya leaf (Carica papaya L.) is one of the plants that is commonly used by the community as a traditional herbal medicine because it contains secondary metabolite compounds that have pharmacological activities such as alkaloids, flavonoids, vitamin C, vitamin A, vitamin B1, sacrose, dextrose, levulose, tannins, proteins, carbohydrates, etc. This study aims to determine the levels of flavonoids contained in papaya leaf extract (Carica papaya L.) and its application as an anti-pain tested in mice (Mus musculus). The research methods used were extraction by maceration method, analysis of flavonoid levels by UV-Vis Spectrophotometry method and its application in test animals was carried out in vivo. Based on the results of the study, the level of flavonoids in papaya leaves (Carica papaya L.) from ethanol extract in coastal areas was 63.89 mgQE/g or 6.39% and ethanol extract in mountainous areas was 74.80 mgQE/g or 7.48%. Furthermore, the most effective analgetic activity of ethanol extract of papaya leaves (Carica papaya L.) was found at the maximum dose concentration.